Normative data on the one-handed static pull strength of a Chinese population and a comparison with American data. Issue 4 (2nd April 2016) - Or, Calvin; Lin, Jia-Hua; Wang, Hailiang; McGorry, Raymond W.
Abstract: We assess the one-handed static pull strength of a Chinese population and compare it to that of an American sample. Fifty men and 50 women in five age groups were asked to exert their maximum one-handed pull strength in three pulling directions (across, front and side) and from four pulling heights (61 cm, 76 cm, waist height and above-shoulder height). The results showed that women had less pull strength than men under all of the conditions tested. The front and side pulling resulted in the greatest pull strength, with a decrease detected when the pulling height was increased. The American sample exhibited greater strength than the Chinese. Body mass and men's handgrip force were also associated with the pull strength. These variables should be taken into account in the development of tasks related to one-handed pulling. Practitioner summary: In this paper, we report a laboratory-based experiment conducted to assess the one-handed static pull strength of a Chinese population and compare the results with those of an American population. The variables associated with pull strength included gender, pulling direction, pulling height, race, body mass and men's handgrip force.